2014
DOI: 10.1111/ped.12371
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hyperglycemia and retinopathy of prematurity

Abstract: Hyperglycemia is an important risk factor for ROP that can be prevented along with other risk factors by accurate supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Hyperglycemia was significant after adjustment for the other risk factors (2,(12)(13)(14)(15) . In the literature, hyperglycemia is regarded as a marker of acute critical state, reflecting its severity and insulin resistance (1,16,17) .…”
Section: Discussionmentioning
confidence: 93%
“…Hyperglycemia was significant after adjustment for the other risk factors (2,(12)(13)(14)(15) . In the literature, hyperglycemia is regarded as a marker of acute critical state, reflecting its severity and insulin resistance (1,16,17) .…”
Section: Discussionmentioning
confidence: 93%
“…Four out of 9 studies provided the mean glucose level of hyperglycemia9212225. Pooling up the data from these 4 studies showed that the mean glucose level was significantly higher in the ROP compared to the non-ROP group (SMD = 0.88, 95% CI: 0.40–1.37, I 2 = 78%, P = 0.0004, Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Seven out of the 9 studies provided primary data on the number of subjects with hyperglycemia and without hyperglycemia in both the ROP and non-ROP groups21222324252627. Pooling up data from these 7 studies showed that hyperglycemia is associated with ROP with an unadjusted OR of 4.16 (95% CI: 2.09–8.29, I 2 = 65%, P <0.0001) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations